Analisis Pengaruh Bauran Pemasaran terhadap Kepuasan Pasien pada Rumah Sakit Khusus Bedah X Kota Padang - Intan Kamala Aisyiah; Nurmaines Adhyka (Jurnal Riset Hesti Medan, 2022)
Hospitals are currently required to maintain their existence in the service field, so that they can maintain consumers or patients by paying attention to every factor that affects patient satisfaction. One of the ways hospitals can do this is by modifying the marketing mix and services that match patient expectations and satisfaction. The purpose of this research was to analyze the effect of the marketing mix on patient satisfaction at the X Surgical Specialty Hospital in Padang. This research was conducted by using a quantitative approach with a cross-sectional design. The study sample was 50 patients or families of adult patients, willing to fill out questionnaires, able to communicate well, and not employees of the X Surgical Specialty Hospital in Padang or their families, who were selected using accidental sampling techniques. The data were analyzed using the Chi-Square statistical test. The results showed that there was a significant influence between the marketing mix (product, price, place, people, physical evidence, process, promotion) on patient satisfaction at the X Surgical Specialty Hospital in Padang. Thus, the X Surgical Specialty Hospital in Padang needs to retain its consumers or patients so as not to switch to other hospitals.